Efficient Control Strategy of Photovoltaic Grid-Connected Microinverters with Improved Topology - Zipei, Cao; Annisa, Binti Jamali; Abdullah, Yassin (Universiti Malaysia Sarawak, 2024)
The microinverter is the core component of modular photovoltaic grid-connected power generation systems. It offers advantages such as convenience, flexibility, high security, and high reliability. However, there are drawbacks of microinverters in terms of service life, conversion efficiency, and cost. This research focused on reducing losses, increasing efficiency, and lowering costs via an improved flyback topology structure and a novel control strategy. This thesis proposed an interleaved parallel passive clamp flyback topology with a compensation capacitor. By adding the compensation capacitor to reduce the switching frequency of the Metal-Oxide-Semiconductor Field Effect Transistor (MOSFET), a passive clamp is used to absorb the leakage inductance energy. Besides, an interleaved parallel topology is introduced to increase output power and suppress ripple, highlighting its stability and cost-effectiveness compared to other flyback topologies. Based on the topology structure, considering the parasitic parameters of various components and referencing various circuit parameters, along with the derived peak current reference curve, a novel multi-valley turn-on strategy is proposed to minimize the voltage stress during the MOSFET turn-on. Additionally, a prototype and experimental platform of a flyback microinverter based on the proposed topology structure and control strategy were constructed. Through simulation and experimentation, it was determined that the interleaved parallel passive clamp flyback topology with compensating capacitors can effectively extend the resonant period by 10.78%, reduce the peak voltage of the MOSFET by 9.8%, decrease the harmonic content by 0.91%, and simultaneously address the issue of component reuse. Based on the multi-valley turn-on strategy, the microinverter achieves valley turn-on under different grid phases, with a maximum efficiency of 97.49% and a stable Total Harmonic Distortion (THD) ranging from 2.22% to 2.59% in the simulation. The final experimental prototype achieves a maximum efficiency of 96.01% at full load, with a THD of the grid current of 2.67%. By comparing simulation and experimental results, this thesis validated the stability of the proposed topology structure and the effectiveness of the control strategy, reducing switch losses, extending inverter lifespan, improving efficiency, and reducing costs. This research can be widely applied in the industrial field of microinverters, translating into practical outcomes and promoting the development of photovoltaic technology.